Distorted Beliefs about Luck and Skill and Their Relation to Gambling Problems and Gambling Behavior in Dutch Gamblers - Cowie, Megan E.; Stewart, Sherry H.; Salmon, Joshua; Collins, Pam; Al-Hamdani, Mohammed; Boffo, Marilisa; Salemink, Elske; de Jong, David; Smits, Ruby; Wiers, Reinout W. (Frontiers in Psychology, 2017)
Gamblers’ cognitive distortions are thought to be an important mechanism involved in the development and maintenance of problem gambling. The Gambling Cognitions Inventory (GCI) evaluates two categories of distortions: beliefs that one is lucky (i.e., “Luck/Chance”) and beliefs that one has special gambling-related skills (i.e., “Skill/Attitude”). Prior psychometric evaluations of the GCI demonstrated the utility of both subscales as measures of distortions and their concurrent relations to gambling problems among Canadian gamblers. However, these associations have not yet been studied in gamblers from other cultures nor have relationships between the GCI and indices of gambling behavior been investigated. In addition, the predictive validity of the GCI scales have not been evaluated in studies to date. The present study investigated the validity of the GCI as a measure of cognitive distortions in a sample of 49 Dutch gamblers by examining its concurrent and prospective relationships to both gambling problems (as measured through a standardized nine-item questionnaire assessing gambling-related problems) and behaviors (as measured through two variables: days spent gambling and time spent gambling in minutes) at baseline and over one-month and six-month intervals. The Gambling Cognitions Inventory subscales were internally consistent at all timepoints, and moderately to strongly inter-correlated at all timepoints. Each subscale correlated with an independent dimension of gambling both concurrently and prospectively: Luck/Chance was related to greater gambling problems and Skill/Attitude was related to greater gambling behavior. Thus, the two GCI subscales, while inter-correlated, appear to be related to different gambling outcomes, at least among Dutch gamblers. Moreover, the first evidence of the predictive validity of the GCI scales was demonstrated over a one-month and six-month interval. It is recommended that both types of cognitive distortions be considered in research and clinical practice to fully understand and address individual risk for excessive and problematic gambling.